Makrodesign of Implant - Types and Shapes of Threads Used and their Evaluation Using Finite Element Analysis - L. Dzan; P. Henyš; L. Čapek; A. Šimůnek (Czech Dental Chamber, 2013)
Introduction, Aim: Mechanical transfer of load onto the bone affects, besides implant material properties (microdesign), especially the type of thread used and its parameters (macrodesign). There are four basic types of thread: a) metric, b) flat, c) saw-tooth, d) inverted saw-tooth and two modified shapes as specified in standard ISO TC 150: e) ISO Shallow HA cortical, and f) ISO Deep HB cancellous. Mechanical transfer is a characteristic of the rate of mechanical stress transfer from thread to bone, which is less than one. The value of one constitutes an ideal situation but due to different strengths and elasticities in the bone and in the thread material, respectively, this value is difficult to achieve.Two objectives were set for the study. The one was to establish stress (tensile, compressive, and shear) distribution with the most used types of dental implant threads at the implant bone contact. The other objective was to characterize mechanical compatibility (or mechanical transfer of load from implant onto adjacent bone) with the same types of thread. Methods: The Finite Element Method using MSC Marc (MSC Software s.r.o.) program and methodology by Amit Gefen were utilized while the entire implant bone contact length was analysed.The model generation process consists of three stages.* Definition of boundary conditions. The load force was F = 100N, direction of force was identical with the implant longitudinal axis while the origin of force was at its cervical area.* Establishing material model characteristics. Isotropic model, specified with two constants, was used to establish characteristics of material properties: Young's modulus of elasticity (E) and Poisson's ratio (μ)* Task specifications. The model was simulated as a 3D axisymmetric task. Results: The ISO Shallow HA thread comes out as the best one from the tensile stress's point of view whereas the flat thread appears to be the most convenient when considering compressive or shear stress. The results computed using the Finite Element Method with all types of threads simulated confirm that the largest part of stress in threaded connection is found in the foremost cervical turns of thread. Discussion and Conclusion: The simulations carried out implicate that the thread cross section shape plays an important role in affecting stress amplitude and distribution adjacent to the bone as well as mechanical compatibility. Our mathematical study does not prove that there is one single ideal type of thread for dental implants.